Transitioning to social health insurance in Pakistan: The experience of Sehat Card Plus in Khyber Pakhtunkhwa province - Sameen Siddiqi; Shifa Salman Habib; Waqas Hameed; Viroj Tangcharoensathien; Adil Haider (Journal of the Pakistan Medical Association, 2024)
Following the experience of many low- and middle-income countries (L&MICs),1 there has been a gradual transition in Pakistan towards public sector financed health insurance, primarily for providing in-patients care. This change has particularly been seen in the provinces of Punjab and KP as well as at the federal level.2 Historically, public sector financing in health has predominantly relied on tax-based financing in Pakistan.3 The health system has remained chronically underfunded with public sector funding hovering around 1% of the GDP and financing has largely relied on direct out of pocket (OOP) payment by the households.4 Khyber Pakhtunkhwa (KP) province embarked on a health insurance reform in 2013, starting in four districts, targetting people living below poverty line as defined by Benazir Income Support Programme (BISP) criteria.5 In 2015, it evolved into a flagship publicly funded social health insurance scheme, Sehat Sahulat Programme, implemented through the State Life Insurance Corporation (SLIC), providing inpatient services, free at point of care, at empanelled hospitals. This was a move away from OOP payments, and promised enhanced financial protection for the beneficiary households.4 In April 2020, the KP government extended the coverage to all households in the province, irrespective of poverty status, and renamed it the Sehat Card Plus (SCP) programme. SCP claims to provide an annual cover of up to PKR 1 million per family with over 7 million enrolled households.5 On the request of the KP government, the Aga Khan University accepted to undertake an independent evaluation of the SCP in 2022-23, which comprised a threetiered assessment supported by GIZ.6 This special issue of JPMA presents a series of 8 papers that summarize the results of the SCP Programme evaluation. To the best of our understanding this is the first comprehensive evaluation of any health insurance programme in Pakistan. Continued...